Pengaruh Vidio Tiktok (Menstruasi) Terhadap Peningkatan Sikap Remaja Putri di SMK Batik 2 - Dipo Wicaksono; Nadya Puspita Adriana (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
In adolescent girls who experience puberty is characterized by the first menstruation (menarche). Menstruation is a release of the uterine wall (endometrium), which is accompanied by bleeding and occurs every month. In menstruating women must remain clean and healthy (personal hygiene), to avoid decay and the development of fungi that can cause infections in intimate organs (cervical cancer and bladder infections). The study aims to improve the assessment of Personal Hygiene (Menstruation) attitudes by using TikTok as a promotional medium. The research design used Quasi Experimental with pre-test and post-test to measure students' attitudes about personal hygiene. This study used a one group design pre-test post-test approach without an ampelous control group in this study as many as 70 respondents. Data analysis using SPSS 23. And there is a difference in the average value (mean) of attitudes before and after intervention through TikTok media, which is 9 points for the value of attitude before intervention is 10.06 points and after intervention is 19.06 points. From the analysis above, we obtained the value of p = 0.001 or < 0005. TikTok media is used to improve the attitude of female students after being given interventions about personal hygiene (Menstruation). There was an increase in scores before and after the intervention for attitude variables.